Application of the MODIPROM method to the final solution of logistics centre location - Marković, Goran; Gašić, Milomir; Kolarević, Milan; Savković, Mile; Marinković, Zoran (Transport, 2013)
Awareness of the role of logistics centres is the precondition for successful planning, optimization, design, management, control and analysis of logistics processes and subsystems. Transportation requirements in supply chains, ecological requirements and the need for quality life in cities particularly emphasize the importance of selection of logistics centre locations, manner and time of supply. Taking into account the significance of selection and ranking of different locations, it is necessary to compare, as objectively as possible, the influences of various criteria and reduce them to a common function, i.e. present the methodology of solving complex problems associated with ranking of alternatives. The proposed method is expected to be a comprehensive tool of decision makers during the selection of the optimal logistics centre locations.First Published Online: 24 Dec 2013